NECK TISSUE REJUVENATION WITH PERCUTANEOUS COLLAGEN INDUCTION, DRUG DELIVERY AND HOME CARE: EXPERIENCE REPORT - Costa Pena, Liz; Rech Feldmann, Cristina (Health and Society, 2022)
Percutaneous collagen induction or microneedling is a procedure that, through the opening of microchannels on the surface of the skin, generates healing induced by platelets that increase the production of growth factors and cytokines, triggered by a controlled inflammation that stimulates the production of collagen and elastin. With the microneedling protocol and the use of drug delivery in mature skin, the results are optimized by the association of specific actives that will be more effectively absorbed by the microchannels. The objective of this work is to carry out a brief literature review and case report on the use of the percutaneous collagen induction method with the association of drug-delivery and home care in the neck region with the aim of superficial and deep tissue rejuvenation. The results found through clinical observation were a significant improvement in the appearance of aging, dryness, superficial flaccidity, fine rhytids, photoaging and devitalized appearance. Little or no results were observed in the improvement of deep flaccidity, horizontal wrinkles and central vertical bands of the neck after 4 sessions of the protocol.